Impact of rural and urban electricity access and economic growth in Ghana: Does line transmission losses matter? - Edward, Amanfo Smart (Energy Economics Letters, 2023)
This paper aimed to estimate the impact of rural and urban electricity access on Ghana’s economic growth between 1993 and 2018 by controlling for electricity transmission losses as a percentage of total electricity transmitted. The study used Stock-Watson Dynamic Ordinary Least Square (DOLS) to estimate the impact of electricity access and transmission losses on Ghana’s economic growth. The Engle-Granger, Phillips-Ouliaris, Park’s added variables and Hansen parameter instability cointegration methods were applied to test the long-run cointegration of the studied variables The results show that a 1% increase in electricity access was associated with a 0.073% decrease in economic growth. Additionally, a percentage increase in the rural electricity access rate was associated with a 0.527% increase in national income per capita. In contrast, urban population electricity access had no statistically significant association with economic growth in Ghana. The study suggests that improving population access to electricity infrastructure services while reducing power wastage through electricity transmission loss minimization is crucial to achieving the long-term impact of electric power on socio-economic development and environmental sustainability in Ghana, subject to other equally essential conditions.